Gastroduodenal artery aneurysm degeneration after coiling necessitating open repair - Madeleine Carroll, MD; Deena B. Chihade, MD; Thomas J. Vandermeer, MD; Anthony Feghali, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
A 77-year-old male presented for an incidental 5-cm gastroduodenal artery aneurysm (GDAA). He underwent an endovascular GDAA coil embolization with 6 months of no aneurysmal growth on surveillance imaging. His 12-month scan revealed aneurysmal growth from 5 cm to 7.5 cm involving the hepatic confluence. He underwent successful open aneurysm resection and primary anastomosis of the hepatic artery. Although less invasive interventions are recommended for GDAAs, many vascular surgeons prefer to proceed with an open repair. Continued GDAA enlargement after perceived endovascular success demonstrates the importance of long-term surveillance and viability of open intervention, sparing patients from a potentially fatal rupture.